ADOBE STRUCTURES AS OUR CULTURAL HERITAGE AND THEIR FEATURES - Tunalı, Selma (European Scientific Journal, ESJ, 2015)
History indicates that the very first homes were built with the use of natural and local materials. Adobe (which is produced from soil) was an important building material and it was used by the groups that established the first settlements. The archaeological excavations (especially in Anatolia and Mesopotamia) continuously prove this indication. At first, humanity led a life in migrant shelters against the harsh and destructive conditions of the nature, but later gave the most beautiful examples of architecture by using materials that he found in his vicinity. Soil has been used as a building material until today and still continues to be so, especially in Anatolia, Mesopotamia, Yemen, Libya. Soil is a very economical material that can be easily shaped. It can keep its form against natural effects and has a very high temperature and permeability resistance. Technological developments have influenced the whole world and provided numerous conveniences and created many positive effects, however they also brought with them a lot of environmental problems that affect the nature and the mankind. To resolve such problems (such as the change in climatic conditions, the increase in temperature and drought, the extinction of some species), the humanity must design structures that are sensitive to the environment. Considering human health and unification with the nature in a building design that is sensitive to the environment, the most suitable material to provide such qualities would be the soil based adobe which has been used both in rural and urban settlements since the Çatalhöyük Neolitik settlement in Anatolia. In this study we will examine structures that were built with soil based material, by giving examples from the past to the present. These structures can be continued not only in Anatolia and Mesopotamia, but also in different parts of the world.